Single pulse avalanche robustness and repetitive stress ageing of SiC power MOSFETs - Fayyaz, A.; Yang, L.; Riccio, M.; Castellazzi, Alberto; Irace, A. (Elsevier, 2014)
This paper presents an extensive electro-thermal characterisation of latest generation silicon carbide (SiC) Power MOSFETs under unclamped inductive switching (UIS) conditions. Tests are carried out to thoroughly understand the single pulse avalanche ruggedness limits of commercial SiC MOSFETs and assess their aging under repetitive stress conditions. Both a functional and a structural characterisation of the transistors is presented, with the aim of informing future device technology development for robust and reliable power system development.